Governance and Financial Performance as Drivers of Bank Profitability in Indonesia - Bagiana, I Kadek (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
The purpose of this study is to empirically examine the relationship between the profitability of banking businesses listed on the Indonesia Stock Exchange (IDX) as evaluated by Return on Equity (ROE), and the following variables: Board Gender Diversity (BGD), Net Interest Margin (NIM), Non-Performing Loans (NPL), and Firm Size (SIZE). The 141 observations used in this quantitative study are based on secondary data extracted from the annual reports of 47 different banking businesses for the years 2021–2023. After the data passed the traditional assumption tests, multiple linear regression analysis was used to examine the data. Analyses show that firm size, gender diversity on the board, and net interest margin all positively affect Return on Equity. Return on Equity, on the other hand, is severely impacted by Non-Performing Loans. There was a statistically significant relationship between bank profitability and each of the four independent factors. Management at financial institutions can learn a lot from the results on the strategic value of diverse boards and careful risk management. This study sheds light on the internal variables that matter most to banks' bottom lines, which is useful information for investors. Theoretically, this research adds to what is already known about the relationship between corporate finance and governance by presenting data from a developing economy.